2015
DOI: 10.1016/j.ygyno.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of differential expression of angiogenic genes in women with high-grade serous ovarian carcinoma

Abstract: Objectives To identify angiogenic biomarkers associated with tumor angiogenesis and clinical outcome in high-grade serous ovarian cancer (HGSC). Methods 51 HGSC samples were analyzed using Affymetrix HG-U133A microarray. Microvessel density (MVD) counts were determined using CD31and CD105. Association between mRNA expression levels and overall survival were assessed using rank score statistic. Effect size was estimated as a hazard ratio (HR) under a proportional hazards model. The Storey q-value method was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
2
26
1
Order By: Relevance
“…In our study, we observed that the increased CD31 expression positively correlated with nodal involvement. In a variety of solid tumors, as well as hematological malignancies, increased angiogenesis is associated with poor prognosis (27,28). Surprisingly, in our study, despite the significant correlation between CD31 expression and MF progression, we did not observe any impact on survival.…”
Section: Discussioncontrasting
confidence: 83%
“…In our study, we observed that the increased CD31 expression positively correlated with nodal involvement. In a variety of solid tumors, as well as hematological malignancies, increased angiogenesis is associated with poor prognosis (27,28). Surprisingly, in our study, despite the significant correlation between CD31 expression and MF progression, we did not observe any impact on survival.…”
Section: Discussioncontrasting
confidence: 83%
“…Of these, high CD44 was associated with longer survival in the TCGA database. In contrast, high expression of EPHB2 and NRP1 were associated with shorter survival in an external database (76). Microarray analysis of cell lines may potentially identify genes that have prognostic significance for survival.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted an extreme phenotype study that included women with long survival (>7 years) vs. short survival (<3 years) (76). Thirty-one genes were significantly associated with clinical outcome including several of the genes reported in our current study ( CD44−, EPHB2, HIF1A, NRP1 , and TGFA ).…”
Section: Discussionmentioning
confidence: 99%
“…In HCC in vitro cells, ANGPTL3 antisense oligodeoxynucleotides inhibit cell proliferation and invasion [37]. ANGPTL3 mRNA level in high-grade serous ovarian carcinoma is associated with shorter survival [38]. In glioblastoma and breast cancer, ANGPTL3 expression in cancer cells provides a predictive factor [39,40], while high ANG-PTL3 expression in renal cell carcinoma (RCC) upregulates in sorafenib-responsive RCC.…”
Section: Angptl3mentioning
confidence: 99%